'APAAN in the neck' – A reflection on some novel impurities found in seized materials containing amphetamine in Ireland during routine forensic analysis. Issue 7 (10th May 2017) - Power, John D.; Kavanagh, Pierce; McLaughlin, Gavin; Barry, Michael; Dowling, Geraldine; Brandt, Simon D.
Abstract : This perspective examines amphetamine importations into Ireland. Some novel by‐products were detected and linked to a change in the method of production of P2P from APAAN. These by‐products remained present during subsequent Leuckart reaction conditions. Novel by‐products from substituted cathinone synthesis reactions were also isolated and characterized.